Developing perennial upland rice. I: Field performance of Oryza sativa/O. rufipogon F1, F4, and BC1F4 progeny. - Sacks, Erik J.; Roxas, Jose P.; Cruz, Maria Teresa Sta. (Wiley, 2003)
Development of perennial upland rice (Oryza sativa L.) could improve food security for subsistence farmers while facilitating the conservation of natural resources, but the feasibility of breeding such a cultivar is unknown. The objective of this study was to determine if O. rufipogon Griff., the wild ancestor of cultivated Asian rice, would be a useful source of genes for introgressing perennial growth habit into cultivated rice. In two trials conducted at the International Rice Research Institute, cultivars were compared with interspecific F1s or with rapidly advanced F4 and BC1F4 families, respectively. After 1 yr, none of the cultivars survived but survival in progeny families ranged from 0 to 85.7%. Average survival for the F1s was 30.6% and only one family out of 31 had no survivors. Correlations between F1 family survival and parental O. rufipogon vigor at 9 mo and 20 mo indicated that at least 1 yr is needed to identify perennial genotypes. Fertility among the progeny was generally good, which should facilitate further breeding efforts. In contrast to the cultivars, which produced only one main crop at the end of the wet season, many progenies produced a ratoon crop during the dry season even though they were drought stressed. The ability to produce a dry season ratoon crop under upland conditions is a new opportunity for increasing food security of subsistence upland rice farmers. Breeding perennial cultivated rice should be feasible but it will likely take 5 to 10 more years.